Caracteríticas dos pesquisadores brasileiros de química e de sua produção científica no período de 1973 a 1977 - Santos, Maria Consuelo Pinheiro (1981)
Analysis of the characteristics of the Brazilian researchers on chemistry and their scientific production in the period 1973-1977, through interpretation of the performance of four variables related to the problem – scientific production, formal education, institutional coverage and information access. The IBICT's directory of researchers on chemistry and the Chemical Abstracts have been the basic tools for data collecting, which after being tabulated showed the relationship among the variables studied according to the percentual, frequencies distribution and the qualitative analysis of the quantitatives data. The results suggest that the variable "information access" influences more directly on the scientific production of the researchers that the others considered in this work.